2017
DOI: 10.4172/2168-9776.1000212
|View full text |Cite
|
Sign up to set email alerts
|

Coppice Forests: Can Traditional Coppice Forest Management Help the Western Balkan Region?

Abstract: Coppice forests are widespread throughout Europe, but in Western Balkan countries these coppice forests play an especially vital role in the everyday lives of their inhabitants. In the Western Balkan region firewood still plays a major role in cooking and interior heating, with about two-thirds of the population using firewood to stay warm rather than using electrical heating. This paper will be an analysis of the current situation of coppice forests in the Western Balkan region and the opportunities that may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Several studies were conducted analyzing structure, functions, silvicultural measures and other aspects in coppice forests in Europe and the Balkan region [1][2][3][4][5][6][7][8]. Authors [3][4][5][6][7][8] from South Eastern Europe (SEE) concluded that degradation and inappropriate treatments in high forests in the 20 th century resulted in degradation and appearance of coppice forests on larger areas. Stajić et al [3] described past and recent coppice forest management in some regions of SEE in relation to their characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies were conducted analyzing structure, functions, silvicultural measures and other aspects in coppice forests in Europe and the Balkan region [1][2][3][4][5][6][7][8]. Authors [3][4][5][6][7][8] from South Eastern Europe (SEE) concluded that degradation and inappropriate treatments in high forests in the 20 th century resulted in degradation and appearance of coppice forests on larger areas. Stajić et al [3] described past and recent coppice forest management in some regions of SEE in relation to their characteristics.…”
Section: Introductionmentioning
confidence: 99%